2015
DOI: 10.3906/sag-1311-91
|View full text |Cite
|
Sign up to set email alerts
|

The effects of atorvastatin on antioxidant/antiinflammatory propertiesof HDLs in hypercholesterolemics

Abstract: Background/aim: Hypercholesterolemia is characterized by changes in lipid profile, nitric oxide pathway, and oxidative stress markers, but functions of high-density lipoprotein (HDL) were not well established in hypercholesterolemic subjects treated with atorvastatin. In this study, we aimed to evaluate effects of atorvastatin treatment on functionality of HDL, oxidative stress, and endothelial functions in hypercholesterolemic subjects. Materials and methods:Thirty patients (20 females, 10 males) aged from 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, no factor was associated with increased ArylE activity on follow‐up. Several other studies have shown an increase in ArylE activity after statin treatment; however, only one was a randomized control study . Since diminished PON‐1 activity is linked to adverse outcomes in patients with HF, targeting those with diminished PON‐1 activity may provide a protective role in HF.…”
Section: Discussionmentioning
confidence: 99%
“…However, no factor was associated with increased ArylE activity on follow‐up. Several other studies have shown an increase in ArylE activity after statin treatment; however, only one was a randomized control study . Since diminished PON‐1 activity is linked to adverse outcomes in patients with HF, targeting those with diminished PON‐1 activity may provide a protective role in HF.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent data show that the basal release of NO and the subsequent endothelial-dependent vasodilation are impaired during the development of hypercholesterolemia [11,12,13,14]. In particular, it has been assessed that local NO release is attenuated in patients undergoing serum levels of LDL up to 160 mg/dL [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In any case, extracting a clinically applicable conclusion is highly speculative, and the often contradictory results on PON1 activity exerted by statins reported in different studies could be explained by the existence of gene polymorphisms among individuals. These would make some patients have higher PON1 levels so they might obtain further benefit from the treatment [65,66].…”
Section: Pon1 and Cholesterol Lowering Drugsmentioning
confidence: 99%
“…The protective effect of statins on endothelial function involves increasing NO biosynthesis and bioavailability via the direct up-regulation of eNOS expression [67]. In contrast to the above-mentioned study of Çiftci et al [65], where atorvastatin behaved as a beneficial pharmacological modulator of impaired endothelial functions by decreasing ADMA levels, some other studies to date indicated that statins have no or little effect on ADMA levels [68,69].…”
Section: Pon1 and Cholesterol Lowering Drugsmentioning
confidence: 99%